Premier League 2020 Player Data Clustering with the DBSCAN Algorithm - Muhammad Thariq Sabiq Bilhaq; Aisyah Amini Nur; Akbar Hidayatullah Harahap; Ihsan Muttaqin Bin Abdul Malik; Muhammad Irfan Nur Imam; Muhammad Nur Sidiq (UIN Sunan Gunung Djati Bandung, 2021)
Premiere League is prestigious event that is in demand by many people. And player goals are very important in this regard. Research on the number of players based on this age can be done. One of which is by clustering. Clustering is a method for grouping objects according to their similarities. And the algorithm used DBSCAN. This algorithm can solve complex problems and has the right density so that it can help to get clustering data on this theme.